Streaming Subjectivation: Two Questions and One Thesis about Netflix - Soares De Moura Costa Matos, Andityas (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
This paper aims to investigate – shortly – the subjectivation process that emerges from Netflix, here understood as a spectacular apparatus that articulates, in a very specific way, the category of “subject”. For this purpose, it uses ideas of authors such as Giorgio Agamben, Roberto Esposito, Michael Hardt & Antonio Negri and Gilles Deleuze. The paper initially delineates a brief theoretical introduction to problems regarding subjectivation and desubjectivation in the post-modernity, especially considering the role played by the new technologies and the new media. Then, it presents two questions about Netflix and its relationship with the guilt, the common and the spectacle. The paper concludes with one thesis: Netflix is a new expression of political theology, since it works dividing and unifying the reality, like the disjunctive synthesis thought by Deleuze. Finally, the text indicates some quick hypothesis that point to a new use – profanatory and careless – of Netflix.